Cultural Perspectives on Religious Tolerance: Exploring Moderation through Texts, Muslim Leadership, and Rituals in Singkawang and Salatiga - Muhammad Rikza Muqtada; Arif Friyadi; Muh Amiruddin (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2025)
This paper examines religious tolerance and moderation in the cities of Singkawang and Salatiga through  cultural perspective. Studies on religious moderation in Indonesia generally focus on regulatory, educational, or theological-normative dimensions. This research offers a new perspective by analyzing religious moderation culturally, emphasizing the role of culture, particularly religious rituals, as instruments of dialogue and collaborative work. This qualitative field research uses functionalism theory to analyze ongoing socio-cultural phenomena, with analytical parameters covering three aspects. First, the aspect of understanding religious texts; second, the role of Muslim religious leaders; and third, ritual/traditional practices. The research findings reveal three main points. First, the interpretations of Muslim leaders in both cities confirm that the values of tolerance, equality, and peaceful coexistence derived from the Qur'an or Hadith remain the foundational principles in responding to the dynamics of a pluralistic society. Second, the experiences of both cities show that moderation grows through responsive leadership, coordinated institutional mediation mechanisms, and interfaith community participation, thereby it forms an ecosystem of tolerance that does not arise spontaneously, but is designed, structured, and sustainable. Third, religious and cultural rituals provide a social space that allows the growth of mutual trust, cooperation, and social cohesion. This research shows that religious moderation is not merely the result of normative teachings, but a practice of living together that is formed through synergy between religious authorities, social leadership, and cultural rituals, which collectively create a more inclusive and resilient pluralistic society against potential conflicts.